Photoluminescent graphene oxide porous particles in solution under environmental conditions produced by hydrothermal treatment - Rivera Tito H.A. (2019)
Photoluminescent graphene oxide particles (PGOPs) were synthesized by hydrothermal treatment. The relative transmission spectra of the PGOPs in the infrared region between 800 cm?1 and 4000 cm?1 showed frequencies that characterize chemical species such as ethers (C[sbnd]O), ketones (CO[dbnd]), carboxylic acids (COOH), double bonds of carbon (C[dbnd]C) and water (H2O). The emission wavelengths were 568 nm for graphene oxide with green photoluminescence (GOGP) and 634 nm for graphene oxide with orange photoluminescence (GOOP) when excited with a light source of 375 nm. Moreover, the detection of light emission at 600 nm in the photoluminescent excitation (PLE) spectrum is detected with more intensity in GOGP than GOOP due to the presence of groups C[dbnd]C and carboxylates ions ([sbnd]COO?) linked to graphene (GN) and the photon effective emission time according to the decay profile for each of them was 9.65 ns and 10.85 ns respectively. PGOPs films made by drop casting at room conditions were observed by Atomic Force Microscopy (AFM) and Scanning Electronic Microscopy (SEM). These films acquire a wrinkled and porous shapes with a pore diameter of 51 nm and roughness (Ra) of Chemically Modified Graphene (CMG) sheets equal to 0.14 nm for GOOP and 0.21 nm for GOGP. © 2019 Elsevier Ltd